(untitled) (Journal of Medical & Health Sciences Review, 2025)
Neonatal sepsis is still a common problem in NICU, and late preterm babies, aged 34 to 36 weeks postmenstrual age are still at high risk due to their immature immunologic system. The identification of the early risk is crucial in the management of patients, but the previously established biomarkers including C-reactive protein (CRP) and Procalcitonin are associated with some drawbacks that affect the accuracy of risk prediction. The aim of this work is to know whether serum albumin levels in LPPN with severe sepsis admitted to NICU in CMH Abbottabad are useful in predicting mortality rates. Randomized controlled clinical trial was conducted during one year, with 100 late preterm neonates with severe sepsis. Serum albumin level was tested on admission, and its association with mortality, length of stay in NICU and mechanical ventilation, and MODS was also determined. The authors found out that the overall mortality rate was higher among neonates with hypoalbuminemia of <3.0 g/dL, 75% as compared to neonates with normal levels, 10% (p < 0.001). The observed differences included a longer length of stay in NICU in the hypoalbuminemic neonates 18.2 ± 5.6 days as compared with 11.4 ± 4.2 days, p < 0.001); mod- ern Trend as identified by MODS was higher in the hypoalbuminemic neonates, (61% vs. 16 %, p < 0.001), and mechanical ventilation was required more in the hypoalbuminemic neonates as 70% compared to 20%, p < 0.001). In ROC, an area under the curve AUC of 0.83 was observed in serum albumin cut off of 3.0 g/dl with the sensitivity of 80% and specificity of 75% thus emphasizing a better test accuracy to predict these adverse outcomes. Specifically, research comparing other biomarkers including CRP and procalcitonin show that serum albumin has better prognosis (AUC= 0.85). Thus, the results call for the implementation of serum albumin assessments as a cost-efficient initial predictor of neonatal sepsis severity. Based on this relationship, it is possible that evaluation of serum albumin levels should be included in the care of neonates with sepsis by providing essential information when making decisions as to the course of actions to be taken. Additional large scale studies should be undertaken to determine whether albumin supplementation will be of benefit in lessening the morbidity of hypoal buminemic septic neonates.